CHANGES IN RAT HORMONES UNDER HYPERTHYROID CONDITIONS AND AFTER PROTECTION WITH OLIVE OIL - Umarkulov B.S. (Central Asian Journal of Medicine, 2025)
Thyroid hormones play an important role in many physiological functions, including the proper functioning of reproductive functions in animals and the regulation of their development. An excess or deficiency of thyroid hormones leads to changes in testicular function. Changes in hormone levels were identified in hyperthyroid rats and during protection with olive oil. When the levels of testosterone and thyroid hormones were analyzed in hyperthyroid rats, it was found that in the first experimental group (i.e., the hyperthyroid condition), the TSH level in the blood was significantly reduced compared to the control group, and the free testosterone level decreased several times, while the T4 and free T4 levels in the blood were increased. In rats treated with L-thyroxine and olive oil, a slight increase in blood TSH and free testosterone levels was observed.